Two-dimensional visual art appearance from the perspectives of Islamic shariah compliant / Ishak Ramli - Ramli, Ishak (2022)
Visual art is one of the fields that continues to thrive in the Arts Industry in Malaysia. Empowering the development of the field of visual art from the aspect of Islamic compliant, is something that needs to be done to avoid matters arising in the future. This applies to other areas too, to ensure each development is in line with the framework of Islamic understanding and knowledge. Based on the existence of ‘Guidelines and Explanations of Visual Art from Islamic Perspectives’ (1987); the discussion is only focused on: 1) the type of drawing (two-dimensional image); and 2) the type of carving (three-dimensional form). Moreover, the discussion of the law was limited to a few types of visual appearance that were believed to be important at the time. Based on the researcher’s observation and the highlights of previous studies, there are research problems and gaps that have been raised and there is a need to improve the ‘guidelines’ that have been produced over the 30 years. Therefore, the objectives of this research are: 1) to identify the visual subject and style of visual appearance practiced by Malaysian visual artists; 2) to validate the visual subject and style of two-dimensional visual art appearance through expert review; and 3) to examine the visual subject and style of visual appearance practiced by Malaysian visual artists from the Islamic Shariah interpretation. Using a qualitative approach through the ‘intrinsic case study’ research design, the researcher has formulated strategies based on research objectives. The first objective was achieved by constructing a comprehensive checklist related to two dimensional visual art appearance (TDVAA) through the process of triangulation of the following data: 1) open-ended interview; 2) documentation of hadith, fatwa, and guideline; 3) observation of physical artifact; and objective 2 was achieved by validated the TDVAA checklist through expert review. After that, the third objective was achieved by using a semi-structured and prolonged case study interview technique. A checklist of TDVAA (finding from objective 1 and 2) was used in the interview session to facilitate experts in the field of Islamic Shariah, which are the Deputy Muftis in the Federal Territory Mufti's Office, to provide views on the diversity of two-dimensional visual art appearance. After analysing the interview data, a comprehensive Islamic Shariah view of TDVAA (as listed in objective 1) was obtained. The results of objective 3 in this research can be a reference for visual art practitioners, students, audiences, and collectors in producing and appreciating visual art who are compliant with Islamic Shariah. Future researchers have the potential to conduct Islamic compliant research in the areas of sculpture, animation, fashion based on the views of the Islamic Religious Council of the States in Malaysia, and the Department of Islamic Development Malaysia (JAKIM). This research practically hopes to change the visual art landscape in Malaysia towards celebrating ‘unity in diversity’ which adheres to the principles of the National Cultural Policy 2021 and the Federal Constitution of Malaysia.